FINANCIAL LITERACY, LOCUS OF CONTROL, FINANCIAL TECHNOLOGY AND FINANCIAL BEHAVIOR: CASE ON UNDERGRADUATE STUDENTS OF MAULANA MALIK IBRAHIM ISLAMIC STATE UNIVERSITY MALANG - Ningtyas, Mega Noerman; Siskawati, Erly Nabila (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
FOMO (fears of missing out) and YOLO (you only live once) have influenced the younger generation, especially Generation Z, to become more consumptive. This is a challenge for Generation Z to maintain good financial management. Several previous studies have shown that several factors influence economic behavior, one of which is financial literacy. The more they understand financial concepts, the more likely he is to do good financial management. Likewise, locus of control plays a vital role in shaping financial behavior. Furthermore, the current pandemic conditions impact the lifestyle changes of generation Z. With financial technology; generation Z tends to become more consumptive. This study aims to examine the financial literacy and locus of control on financial behavior with financial technology as moderation. This research was conducted on 389 active students of Maulana Malik Ibrahim Islamic State University Malang by distributing online questionnaires. The results showed that financial literacy and locus of control positively and significantly influence financial behavior. Financial technology can also strengthen the influence of locus of control on financial behavior. However, financial technology is not able to moderate financial literacy on financial behavior.